Characterization of sewage sludge ash and its effect on moisture physics of mortar. (January 2019) - Krejcirikova, Barbora; Ottosen, Lisbeth M.; Kirkelund, Gunvor M.; Rode, Carsten; Peuhkuri, Ruut
Abstract: A study was carried out to investigate the potential use of ash obtained as an incinerated by-product in sewage sludge treatment, as a possible supplementary cementitious material. Chemical parameters and granulometry of the sewage sludge ash and selected physical and hygroscopic properties of cement-ash-based mortar are presented and compared with results from previous studies. The effect of different ratios of cement substitution and two pre-treatment methods for ash, i.e. ash grinding and water washing, on the physical properties of mortar were investigated by using density, porosity and compressive strength as elemental indicators of the mortar quality. The hygroscopic sorption properties of the individual constituents alone and the resulting mortar samples were described by sorption isotherms for water vapour and by a capillary water absorption test. Results showed that the SSAs typically consisted of larger particles compared to the cement particles. Incorporation of ash resulted in more porous mortar structures compared to cement-based mortar, which affected the material's mechanical properties such as the compressive strength. 28-day compressive strength decreased with increasing ash content and porosity. Cement conveyed the greatest ability to adsorb and react with water and there were clear differences between the different ashes. Despite the differences in sorption properties between the different constituents, the effect of ash content on mortar sorption isotherms was negligible. Highlights: High content of P2 O5 was detected in both SSAs. SSAs contained larger and more irregular-shaped grains when compared to cement. SSA content clearly increased mortar porosity and water absorption. SSA content caused a significant decrease in 28-day compressive strength of mortar. Differences of SSAs and cement absorption had limited effect on mortar adsorption.